Diskursus Gender dan Dakwah di Era Revolusi Industri 4.0 - Uswatun Niswah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2021)
The Industrial Revolution 4.0 Era is a golden opportunity for woman to develop their potential to be equal to men in various fields. This paper aims to discuss the history of feminists in fighting for gender equality both globally and in the development of gender discourse in Indonesia. In realizing gender equality, women empowerment programs need to be presented in unique, innovative, and creative way according to women’s needs. Gender and Da’wah Discourse in the Industrial Revolution 4.0 Era can be realized in the form of da’wah for the women empowerment through education or training with community-based, so that women can carry out their roles proportionally and professionally. Da’wah for the women empowerment in the industrial revolution 4.0 era is expected to be able to invite, foster and guide women to develop their potential to be able to be productive, creative and financially independent without having to leave their roles as an individual, wife and mother. Da’wah for women empowerment as an effort to achieve gender equality need to pay attention to the segments and needs of each group of women being fostered, such as the community of young women, the community of housewives and the community of career women.